Hacker News new | past | comments | ask | show | jobs | submit login

From a very quick glance at page 6 of https://arxiv.org/pdf/2310.05328.pdf

You can see he is treating the case of k=1,2 with that formula and uses induction to extend it to 1 ≤ 𝑘 ≤ 𝑛 − 2.

For k = n - 1 he uses a different bound defined in equation 2.2. So he bypasses the issue.




Consider applying for YC's Spring batch! Applications are open till Feb 11.

Guidelines | FAQ | Lists | API | Security | Legal | Apply to YC | Contact

Search: